Anthropometric Characteristics of Underprivileged Adolescents: A Study from Urban Slums of India. (23rd December 2014) - Khopkar, Sushama A.; Virtanen, Suvi M.; Kulathinal, Sangita
Abstract : Purpose . The anthropometric status and growth of adolescents living in challenging conditions such as slums are insufficiently studied. The purpose here was to describe anthropometric characteristics and nutritional status of adolescents from urban slums of India and to study the factors affecting it. Methods . Anthropometric, socioeconomic and dietary habit data were collected using structured questionnaires of six hundred adolescents aged 10–19 years by house-to-house survey conducted in two randomly selected slums of Nashik, Western India. The growth of adolescents was compared using WHO and Indian reference populations. Mixed effects logistic regression models were used to examine associations between anthropometric measures and income, mother's education, household size, and dietary intake. Results . Prevalences of stunting and thinness were lower using the Indian reference population compared to that of WHO. Stunting was more prevalent than thinness in the study subjects, and boys suffered more than girls. The effect of age on stunting was different among boys than girls. A mother's education was highly significantly associated with both stunting and thinness in both sexes. Household size and income were significantly associated with the nutritional status of girls. Conclusions . Educating mothers about the nutritional needs of adolescents may help to improve adolescents' anthropometric profile and future health.